General stabilization of a thermoelastic systems with a boundary control of a memory type - SEMCHEDINE, Nesrine; BENSERIDI, Hamid; DRABLA, Salah (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
In this paper we consider an n-dimensional thermoelastic system, in a bounded domain, where the memory-type damping is acting on a part of the boundary and where the resolvent kernel k of −gt(t)/g(0) satisfies ktt(t) ≥ γ (t) (−kt(t))p, t ≥ 0, 1 < p < 3 . We establish a general decay result, from which the usual exponential and polynomial decay rates are only special cases. This work generalizes and improves earlier results in the literature. Mathematics Subject Classification (2010): 35B35, 35L55, 74D05. Received 22 October 2019; Accepted 21 January 2020.